Inovasi-Inovasi Pelayanan Publik Untuk Pengembangan Ekonomi Lokal: Pengalaman Beberapa Daerah - Agus Pramusinto (Magister Ilmu Administrasi Publik, 2006)
The Indonesian government has been applying a wide-ranged decentralisation policy since 1999. However, many people have seen it from a very negative perspective. They view that local autonomy has brought about little kings that tend to abuse power surrendered by the central government. Local autonomy has also been misused to create discriminatory policies which disseminate primordialism. Veg few people see the local autonomy poligfrom the positive side. This paper discusses the innovation created by local governments in responding to the authority received from the central government. Some local governments have caught this opportunity to develop that improve public services to invite investors. Various cases are discussed to show that some local governments are very serious to reform their policies. However, a case study of Lebak district will be presented to comprehend the implementation deeply. Lebak is a small and poor district (kabupaten) in Banten Province that has developed Kantor Pelayanan Perijinan Terpadu (Integrated Licensing Service Office) that is expected to enhance its local econony. By showing the case of Lebak,people can learn something that can be applied in other districts.